Impact of 5G Technology on IoT Networks Performance: An Analytical Study of information technology on Smart Cities - Ahmed Elstial; Salma Albahlul (African Journal of Advanced Pure and Applied Sciences, 2025)
The rapid increase of using Internet of Things (IoT) devices in smart cities has created unusual demands for network infrastructure suited to support large connection, ultra-low latency, and high-throughput communications. This study shows a full analytical and fundamental impact of fifth generation (5G) wireless technology on IoT networks performance within smart city environments. Based on MATLAB simulations, theoretical analysis, critical performance measurements including latency minimization, throughput improvement, energy efficiency enhancement, and massive device connectivity capabilities were tested. The methodology used a multi- combining approach, network slicing optimization, massive Multiple Input Multiple Output (MIMO) beamforming analysis, and edge computing combination estimating 5G’s performance advantages over legacy 4G LTE systems. Simulation results show that 5G technology achieves impressive improvements in IoT network performance, with latency reductions of up to 79.4% (from 64ms to 13ms average), throughput enhancements reaching 1000 Mbps for enhanced Mobile Broadband (eMBB) applications, and energy efficiency gains of 74% compared to 4Gimplementations. The study shows that 5G’s network slicing capabilities enable optimized resource allocation for verity IoT service types, with Ultra Reliable Low Latency Communications (URLLC) getting 99.999% reliability and massive Machine Type Communications (mMTC) supporting device densities up to 20,000 devices per square kilometer. As well as the analysis appears that 5G-enabled Multi Access Edge Computing (MEC) reduces data processing delays by 35% while maintaining seamless connectivity for time-critical smart city applications. These findings provide substantial evidence for 5G’s role as a foundational technology for next-generation smart city infrastructure, enabling innovative IoT services in transportation, healthcare, environmental monitoring, and public safety domains.